An analysis of meat demand in Argentina using household survey data - Pace Guerrero, Ignacio (2015)
This paper presents an empirical analysis of demand for meat using micro data from three household surveys conducted over the last two decades in Argentina. We present an estimation of a complete demand system for meat using a Quadratic AIDS model. Data of the three household surveys are used: 1996/97, 2004/05 and 2012/13. The Shonkwiler and Yen (1999) methodology is used to correct selection bias and endogeneity of the total expenditure is corrected using instrumental variables. Quality-adjusted prices were obtained following Cox and Wohlgenant methods (1986). Expenditure and price elasticities (compensated and uncompensated), for each period were obtained. We found that beef is the relatively most inelastic good with a higher elasticity observed in the last years. Poultry price elasticity decline 50% and the demand of pork has changed from relatively inelastic to elastic. Poultry appears as the main substitute for all types of meat.